Significance of appetite hormone ghrelin and obestatin levels in the assessment of the severity of acute pancreatitis - Kanat, Burhan Hakan; Ayten, Refik; Aydın, Süleyman; Girgin, Mustafa; Çetinkaya, Ziya; İlhan, Yavuz Selim; Yur, Mesut; Çatak, Zekiye (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Due to risk of morbidity and mortality, various tests and scoring systems used in the assessment of the diagnosis and severity of acute pancreatitis disease are gaining more importance every day. Most of the current scoring systems, validated by various parameters, have a sophisticated and complex structure. Research is ongoing to establish a method to diagnose the disease and determine the severity by using different and simple parameters. In this trial, we aimed to investigate the role of the orexigenic “ghrelin” and anorexigenic “obestatin” hormones, if any, on the diagnosis and assessment of the severity of acute pancreatitis. Materials and Methods: A total of 30 patients hospitalized between September 2009 and September 2010 with a diagnosis of acute pancreatitis (AP) and 25 healthy volunteers were enrolled in the trial with a prospective and randomized design. The patients were classified in two groups, mild (Ranson ≤3 and / or Apache II ≤8) and severe (Ranson >3 and/or Apache II >8) cases, as per the Ranson and Apache-II criteria; the ghrelin and obestatin levels in blood samples obtained from the patients were measured using the ELISA method. Results: Twenty-two of the 30 patients (73%) were regarded as mild pancreatitis cases, while 8 cases (27%) were diagnosed as severe pancreatitis. Comparison of the mild and severe pancreatitis groups did not reveal a statistical difference between the two groups in terms of acylated and de-acylated ghrelin values on presentation and following the initiation of oral feeding. Similarly, no significant difference was found in the comparison of the patient and the control groups in terms of acylated and de-acylated ghrelin values on presentation (p=0.863). On the other hand, acylated and de-acylated ghrelin values after initiation of oral feeding were observed to be higher in the patient group (p=0.001, p=0.000). Comparison of these two groups revealed a significant difference in obestatin values, both on presentation and after initiation of oral feeding (p=0.002 and p=0.000). Conclusion: Consistently high serum ghrelin values during pancreatic inflammation suggest that ghrelin may be used as an adjunctive parameter in the monitoring of the course of the disease. On the other hand, high obestatin values in patients on presentation indicate that this hormone is a more significant parameter in terms of diagnosis. However, no correlation was established between these two peptide hormones and the severity of AP.